Advanced studies on extended spectrum beta-lactamase producing Enterobacteriaceae in dairy cattle farms at Behaira province - Alaa, Omer A.; Elzeftawy, Hoda M.; Salama, Hanaa F. (Journal of Advanced Veterinary Research, 2024)
The rise of bacteria resistant to antibiotics, such Escherichia coli and Klebsiella species, in milk poses a severe threat to public health since milk is widely regarded as a complete food and is a staple of the daily diet of people, especially those in Egypt. Beta lactamase with an extended spectrum (ESBL). Therefore, the purpose of this study was to investigate the prevalence and characteristics of K. pneumoniae and E. coli that produce ESBLs in dairy cattle and milk farms. In this investigation, a total of 150 milk samples were cultured on VBGR, MacConkey, and Hichrome to isolate these bacteria, and antibiotic resistance was evaluated by using the double disc diffusion technique. Subsequently, biochemical and serotyping testing were used to confirm and identify the suspicious microorganisms. Using a PCR test that targets blaCTX-M, ESBL producers were identified. Of the samples tested, 34 (22.7%) tested positive for K. pneumoniae in milk,Â and 21 (14%), positive for E. coli. Different ETEC serotypes (O128:H2 and O127: H6) and EHEC serotypes (O91: H21 and O26: H11) were found contaminated in milk. Additionally, 21 samples (67.7%) had K. pneumoniae serotype B1 as the prevalent serotype. Most isolates had the Î²-lactamase blaCTX-M gene, which has become more significant among bacteria that produce ESBL globally. blaCTX-M gene was detected in 65% of E. coli and 80% of K. pneumoniae. Thus, given the trend of farmer-to-consumer direct marketing, raw milk is a possible source of exposure for the consumerâ€”something that is becoming increasingly important. Lastly, calves may potentially acquire ESBL-producing bacteria via waste milk, which would increase the prevalence of antibiotic resistance in the agricultural setting.